AlfaOne Application Redesign Using Lean UX Method - Anjeli, Saiba; Try Hafsani, Yuke; Efendi, Yoyon; Tashid, Tashid; Utami, Nurul (Prosiding Seminar Nasional Ilmu Komputer, Sosial Sains, Teknik dan Multi-Disiplin Ilmu, 2025)
AlfaOne application is a digital service application owned by PT Sumber Alfaria Tri Jaya TBK which not only provides transaction features, but also various supporting services that make it easier for users to carry out daily activities digitally. This application is designed to increase ease of access to services for users without having to come directly to physical outlets. The existence of the AlfaOne application is expected to increase service effectiveness, reduce queues at outlets, and encourage increased use of digital services. However, based on the results of initial observations, the features and interface design of the AlfaOne application are considered less than optimal and less attractive, resulting in a decrease in user interest and comfort in using the application. Therefore, a redesign of the user interface (UI) and user experience (UX) is needed as a basis for building a platform that is more attractive, easy to use, and in accordance with user needs. The Lean UX method was chosen in this study because it focuses on user satisfaction through an iterative, collaborative, and user feedback-based design process. Based on the results of the analysis, implementation, and evaluation, this study produced a final prototype which is a combination of prototype A and prototype B which has been validated in terms of appearance, functionality, as well as criticism and suggestions from users and technical parties. Prototype A was selected for 3 features and prototype B was selected for the other 3 features. On the login page, design B was selected with a percentage of 53%, the home page was selected with a percentage of 57%, and the history page was selected with a percentage of 62%. In addition, the results of the study showed that the proposed interface design has consistency in the use of color, typography, icons, and layout, and provides a more understandable user experience in accessing features and information as needed. The final design was tested using the Usability Testing method to measure the level of ease of use and user acceptance of the proposed alfaone application design.